IMPULSE BUYING BEHAVIOR DURING THE COVID-19 PANDEMIC WITH CASH ASSISTANCE FROM THE GOVERNMENT - Adiputra, Eka; Hidayati, Dina Alafi (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2024)
The distribution of government cash assistance during the pandemic for people affected by Covid-19 is aimed at easing the economic burden of the community. However, the provision of cash assistance is indicated not to be used to alleviate needs; aid funds are used to meet hedonic needs. This study determines whether the social assistance funds are consistent in meeting the needs of life or only for hedonic desires. A study was conducted on the effect of hedonic shopping and money available on impulse buying. Samples were 213 respondents. This study uses SEM PLS. The results of this research showed that hedonic shopping positively affected impulse buying. However, money available does not affect impulse buying. Positive emotion will further strengthen hedonic shopping and money available in impulse buying. This study concludes that it is not proven that cash transfer funds are used to fulfil impulse buying behaviour. However, if people with hedonic shopping and money available characters receive an in-store stimulus, they are vulnerable to impulse buying. Future research of this study is to compare impulse buying behaviour in people in big cities and small cities.